PENINGKATAN KUALITAS PRODUK BOOTH DISPLAY MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) DAN PERANCANGAN TOOL DESAIN PRODUK MENGGUNAKAN MORPHOLOGICAL CHART - Veronica Okta Marcelinawati; Anita Indrasari (Universitas Veteran Bangun Nusantara, 2021)
A company must provide quality products that can provide satisfaction to consumers. Therefore, it is crucial to know the consumer's desire to increase customer satisfaction. The objective of this research is to acquire the display booth's product specifications and to design a tool that contains alternative product designs that can help consumers make decisions for the display booth. The method used in this research is the Quality Function Deployment (QFD) method to determine product specifications based on consumer desires and the Morphological chart method for designing product design tools. Based on research using the QFD method, the product specifications of the display booth were obtained, namely, the product shape (8.31), raw materials (7.50), product size (6.11), completeness of product components (5.15), surface texture (2, 14), and color (0.99). These specifications are used for product design tools using the morphological chart method. The tools designed have five alternative designs for each product specification. Suggestions for further research should afford to use science and other approaches to improve product quality and redesign tools that can make it easier for consumers and companies.